1999
DOI: 10.1007/s002489900152
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Radiation (UVR) Sensitivity Analysis and UVR Survival Strategies of a Bacterial Community from the Phyllosphere of Field-Grown Peanut ( Arachis hypogeae L.)

Abstract: > Abstract The short-term population dynamics of the culturable bacterial community from field-grown peanut (Arachis hypogeae L.) was analyzed over three 2-day periods. As in other phyllosphere studies, significant numbers of pigmented organisms were detected, suggesting the importance of pigmentation in the colonization of this habitat. Isolates were grouped according to pigmentation (orange, pink, yellow, nonpigmented), and the sensitivity of each isolate in the collection (n = 617) to ultraviolet radiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
89
3
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(97 citation statements)
references
References 36 publications
2
89
3
3
Order By: Relevance
“…Reflective of marked differences in the physicochemical environments of above-ground versus subterranean plant surfaces, the leaf bacterial flora differs substantially from that of roots. For example, pigmented bacteria, which are rarely found in the rhizosphere, dominate leaf surfaces (28,103,104), presumably because solar radiation influences the ecology of the phyllosphere (45,112). The differential composition of leaf and root bacterial communities is further evidenced by the failure of common root colonizers such as Rhizobium (89) and Azospirillum (51) to become established on leaves.…”
Section: Microbial Communities On Leavesmentioning
confidence: 99%
See 1 more Smart Citation
“…Reflective of marked differences in the physicochemical environments of above-ground versus subterranean plant surfaces, the leaf bacterial flora differs substantially from that of roots. For example, pigmented bacteria, which are rarely found in the rhizosphere, dominate leaf surfaces (28,103,104), presumably because solar radiation influences the ecology of the phyllosphere (45,112). The differential composition of leaf and root bacterial communities is further evidenced by the failure of common root colonizers such as Rhizobium (89) and Azospirillum (51) to become established on leaves.…”
Section: Microbial Communities On Leavesmentioning
confidence: 99%
“…Indeed, a striking feature of epiphytic bacteria is the large proportion that are pigmented (28,103); such pigmentation has been presumed to confer protection against UV radiation. A recent detailed examination of the epiphytic bacteria present on peanut plants exposed to high fluxes of UV revealed that most tolerated relatively large UV fluctuations (112). Interestingly, the relative proportion of UV-tolerant strains in the bacterial community in- creased during those parts of the day when leaves were exposed to UV, and the most tolerant strains were those that produced pink or orange pigments (112).…”
Section: The Leaf Surface As a Microbial Habitatmentioning
confidence: 99%
“…3). Indeed, the abundance of chromogenic species common to the phyllosphere (e.g., Erwinia herbicola [renamed Pantoea agglomerans; however, we will refer to the bacterium by the more familiar name E. herbicola], xanthomonads, fluorescent pseudomonads, and pink-pigmented facultative methylotrophs) has led to the yet unresolved speculation that pigment production may confer a selective advantage to bacteria that colonize a habitat which is exposed to solar radiation daily (58,182,251,272). At present there is some effort under way to determine if UV radiation affects the survival or fitness of bacteria in the phyllosphere (273).…”
Section: The Playersmentioning
confidence: 99%
“…On arrival, new immigrants are challenged with the harsh conditions of the leaf environment (11,12), including highly fluctuating water availability, exposure to UV radiation from sunlight, and limited access to nutrient resources. To cope with these conditions and to survive the leaf environment, microorganisms have adopted different strategies (13) such as the production of pigments to protect against the effects of UV radiation (14) or the secretion of polysaccharides to prevent desiccation when water becomes scarce (15,16).…”
mentioning
confidence: 99%